Relationship between ultrasonically measured beef cow carcass traits and lifetime productivity - L.A. Pacheco; John R. Jaeger; Jennifer Bormann; K. C. Olson (Kansas Agricultural Experiment Station Research Reports, 2011)
Ultrasound is widely used in seed stock production, commercial operations, and in feed yards to predict carcass merit. It also has been used to assess the value of individuals as parents in the seed stock industry. Ultrasound has several advantages as a technique to evaluate body composition: it is relatively inexpensive; it produces results more rapidly compared to progeny testing programs; and data are less prone to selection bias than direct carcass data collection. Ultrasound measures of ribeye area and proportion of intramuscular fat are accurate predictors of their corresponding carcass traits in fed slaughter cattle. Thus, average heritability estimates of ultrasonically measured ribeye area and intramuscular fat are moderate to high. Moderate to high heritability allows seed stock breeders to select replacement animals with confidence based on ultrasound measurements.
Keywords: Kansas Agricultural Experiment Station contribution; no. 11-171-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1047; Cattlemen' s Day; 2011; Beef; Carcass traits; Ultrasound; Progeny performance